Use of a Thermophile Desiccation-Tolerant Cyanobacterial Culture and Os Redox Polymer for the Preparation of Photocurrent Producing Anodes - Gacitua, Manuel; Urrejola, Catalina; Carrasco, Javiera; Vicuña, Rafael; Srain, Benjamín M.; Pantoja-Gutiérrez, Silvio; Leech, Donal; Antiochia, Riccarda; Tasca, Federico (Frontiers in Bioengineering and Biotechnology, 2020)
Oxygenic photosynthesis conducted by cyanobacteria has dramatically transformed the geochemistry of our planet. These organisms have colonized most habitats, including extreme environments such as the driest warm desert on Earth: the Atacama Desert. Cyanobacteria highly tolerant to desiccation are of particular interest for clean energy production. Due to their ability to withstand long periods of desiccation and to perform oxygenic photosynthesis, these microorganisms are promising candidates for designing bioelectrodes for photocurrent generation. Here we present bioelectrochemical assays in which graphite electrodes were modified with the extremophile cyanobacterium Gloeocapsopsis sp. UTEXB3054 for photocurrent generation. Our electrochemical experiments allowed us to determine optimum working conditions for photocurrent production using the cyanobacterial culture assisted with an external redox mediator of osmium polymer. Besides determining the best performing bioelectrode achievement, our results provide new insights into the metabolic basis of photocurrent generation and the potential applications of such an assisted bioelectrochemical system in a worldwide scenario in which clean energies are imperative for a sustainable development.